Fungi and their Role in Sustainable Development: Current Perspectives (Springer Singapore, 2018)
This book illustrates the multiple roles of fungi in everyday life. Fungi are the large group of organisms with tremendous diversity and economic importance. Their ability to produce commercially efficient useful products makes them the vulnerable sustainable tool for the future generation. This book describes a systems approach and provides a means to share the latest developments and advances about the benefits of fungi including their wide application, traditional uses, modern practices, along with designing of strategies to harness their potential. The chapters are organized with data, providing information related to different sustainable aspects of fungi in agriculture, its cultivation and conservation strategies, industrial and environmental utilization, advanced bioconversion technologies and modern biotechnological interventions. Updated information and current opinion related to its application for sustainable agriculture, environment, and industries as futuristic tools have been presented and discussed in different chapters. The book also elucidates a comprehensive yet a representative description of the challenges associated with the sustained application of fungi to achieve the goals of sustainability.